Perancangan Kursi Dan Meja Untuk Pendidikan Anak Usia Dini (Paud) Yang Ergonomis (Studi Kasus Pada Tk. Prime Montessori School Batam) - Robi Edo Saputra; Elva Susanti, S.Si., M.Si (LPPM Universitas Putera Batam, 2020)
Chairs and tables are school facilities that affect the attitude of sitting learners while learning. Based on research on TK. Prime Montessori school Batam students it is known that the size of chairs and tables are not in accordance with the dimensions of the learner's body, namely the seat is too high, the length of the seat is too long, the seat is too wide, the backrest on the seat is too high, the seat has no foam pads on the base and Backrest, table height is too low, the distance between the table and the seat base is too narrow. From the research, conducted research to redesign the ergonomic chair and table. In this study, data collection of anthropometry of 40 data and measuring the chair and table that is currently used the school. The anthropometric data obtained were statistically tested, ie data uniformity test, normality test, data adequacy test and percentile calculation. The results of the calculations are used to perform the design using the software Creo 5.0. The results of this study are the design of chairs and desks are comfortable and in accordance with the anthropometry of learners.